The Swedish Version of the TeamSTEPPS® Teamwork Perceptions Questionnaire (T-TPQ): A Validation Study - Hall-Lord ML; Skoogh A; Ballangrud R; Nordin A; Bååth C (Journal of Multidisciplinary Healthcare, 2020)
Marie Louise Hall-Lord,1,2 Annika Skoogh,1 Randi Ballangrud,2 Anna Nordin,1 Carina Bååth1,3 1Department of Health Sciences, Faculty of Health, Science and Technology, Karlstad University, Karlstad, Sweden; 2Department of Health Science, Faculty of Medicine and Health Sciences, Norwegian University of Science and Technology, Gjøvik, Norway; 3Faculty of Health and Welfare, Østfold University College, Fredrikstad, NorwayCorrespondence: Carina BååthDepartment of Health Sciences, Faculty of Health, Science and Technology, Karlstad University, Universitetsgatan 2, Karlstad 651 88, SwedenTel +46 54 7002089Email carina.baath@kau.sePurpose: The delivery of effective and safe healthcare to patients is highly dependent on careful collaboration between healthcare professionals. Although teamwork is an important component for patient safety, effective teamwork is not always carried out in hospital wards, leading to negative consequences for the patients. Teamwork measurements can be used to evaluate and provide feedback to healthcare professionals to support team performance and to identify areas for improvement. The TeamSTEPPS® Teamwork Perceptions Questionnaire (T-TPQ) evaluates Team Structure and four core competences of teamwork (Leadership, Situation Monitoring, Mutual Support, and Communication) among healthcare professionals in various healthcare settings. The questionnaire was judged to be relevant in a Swedish healthcare context and was translated into Swedish. This study aimed to test the reliability and construct validity of the Swedish version of the T-TPQ.Methods: A total of 450 (of 1176) frontline healthcare professionals working at four hospitals responded to the questionnaire. A confirmatory factor analysis was carried out to test the factor structure. Cronbach’s alpha was used to measure internal consistency.Results: The hypothesized five-factor model of the five dimensions showed acceptable goodness-of-fit indexes. Cronbach’s alpha coefficient for the total T-TPQ was 0.94, and the Cronbach’s alpha coefficients for the dimensions ranged from 0.79 to 0.92. The intercorrelation coefficients ranged from 0.27 to 0.74.Conclusion: The Swedish version of the T-TPQ showed acceptable reliability and validity for measuring healthcare professionals’ individual perceptions of teamwork at the group level. Due to the low response rate, further studies are required to test the validity of the Swedish T-TPQ.Keywords: healthcare professionals, perceptions, questionnaire, teamwork performance, validation study